2019
DOI: 10.1097/cmr.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events of anti-programmed death 1 antibodies combined with anti-cytotoxic T-lymphocyte-associated protein 4 therapy use in patients with metastatic melanoma

Abstract: To date, cutaneous toxicities of combination therapies of anti-programmed death-1 (anti-PD1) and ipilimumab are poorly described. Understanding cutaneous presentations will aid clinicians with early diagnoses and treatments. We aim to describe and compare the cutaneous toxicities between the combination therapies and anti-PD1 monotherapy. This is a cohort study comparing previously published data on 82 patients with metastatic melanoma on anti-PD1 monotherapy, with a new group of 25 patients with metastatic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Leukoderma is an adverse effect of melanoma immunotherapy with check-point inhibitors (Figure 2), with a reported incidence ranging from 3.4% to 28% and a mean onset delay of 30 weeks after therapy initiation [64][65][66][67]. However, even if skin depigmentation is classified as a grade 2 irAE, its appearance does not require therapy discontinuation and could not always be reported.…”
Section: Check-point Inhibitorsmentioning
confidence: 99%
“…Leukoderma is an adverse effect of melanoma immunotherapy with check-point inhibitors (Figure 2), with a reported incidence ranging from 3.4% to 28% and a mean onset delay of 30 weeks after therapy initiation [64][65][66][67]. However, even if skin depigmentation is classified as a grade 2 irAE, its appearance does not require therapy discontinuation and could not always be reported.…”
Section: Check-point Inhibitorsmentioning
confidence: 99%
“…According to recent studies, cuAEs are observed in 70%-88% of the patients, 4,5,38 most commonly non-specific rash, pruritus, lichenoid reactions and vitiligo. 47 They appear earlier and develop more rapidly compared to anti-PD1 monotherapy. 47 It is hypothesized that ipilimumab accelerates the lymphocytic damage to peripheral tissues, thereby causing cutaneous eruptions earlier.…”
Section: Combined Ctla4 and Pd-1 Blockadementioning
confidence: 99%
“…PD-1-targeting monoclonal antibodies have been approved for clinical use and are currently among the first-line treatment options for advanced melanoma patients and many other cancers (28,29). In a fraction of melanoma patients (ranging from 3.4 to 28%), vitiligo-like depigmentation (or melanoma-associated leukoderma) occurs as an adverse effect of immune checkpoint inhibition, indicating the breaking of tolerance to melanocytic self-antigens (30,31). Nevertheless, skin depigmentation has now been reported in anti-PD-1/PD-L1 treated patients with other metastatic cancers as well (32)(33)(34)(35)(36)(37).…”
Section: Melanoma Immunotherapymentioning
confidence: 99%